Assessing Urban Sprawl and Agricultural Land Loss: A 40-Year Remote Sensing Study in Çanakkale - Özelkan, Emre; Eren, Esra (Journal of Contemporary Urban Affairs, 2025)
This study investigates the spatial expansion of rapid urbanization and its pressure on agricultural and natural lands within a socio-economic framework. Covering a 40-year period from 1984 to 2024, the research focuses on the central district of Çanakkale and employs spatial analysis methods alongside regression models. Findings reveal significant losses in agricultural lands adjacent to the city center due to urbanization, coinciding with rising employment in industrial and service sectors. Land use and cover maps for multiple years were produced from remote sensing data, achieving classification accuracy above 85% and kappa coefficients exceeding 0.80, ensuring analytical reliability. Regression results indicate a strong negative correlation between employment in the service sector and agricultural land (r = -0.82, p < 0.05), highlighting the role of economic transformation in rural land use change. The study demonstrates that urbanization should be understood not only as physical growth but as a process intertwined with economic restructuring and social change. By integrating spatial transformations with socio-economic dynamics, it offers insights into balancing development with the protection of productive land. The findings contribute to contemporary debates on inclusive, resilient, and sustainable urban environments, enriching the academic literature on the socio-economic dimensions of urban transformation.